Harnessing the potential of recombinant human BMP2: regulating scleral changes in myopic guinea pigs - Liu, Yijie; Hao, Qi; Pan, Xuemei; Wang, Pubo; Guo, Dadong; Tian, Qingmei; Zhang, Xiuyan; Lu, Xiuzhen; Wu, Qiuxin; Bi, Hongsheng (Frontiers in Medicine, 2025)
Studies have shown that the development of myopia is associated with scleral remodeling, but the exact mechanism is not yet clear. This study investigates the effects of vitreous injection of recombinant human bone morphogenetic protein 2 (rhBMP2) on scleral remodeling in myopic guinea pigs and the possible signaling pathways. Guinea pigs were randomly divided into normal control (NC) group, lens-induced myopia (LIM) group, rhBMP2 low-dose group (LD), rhBMP2 medium-dose group (MD), and rhBMP2 high-dose group (HD). After rhBMP2 intervention, myopic refraction was reduced and axial growth was delayed compared with the LIM group; Hematoxylin–eosin (H&E) staining showed that the arrangement of scleral collagen fibers was loose, the disorder was improved, and the cavities were reduced, especially in MD group; and immunofluorescence staining showed elevated α-SMA protein expression. Q-PCR and western blot results showed that after rhBMP2 intervention, at the mRNA and protein levels, the expression of BMPRIA, smad1, smad5, smad9, smad4, TIMP2, and Col1A1 was up-regulated, and MMP2 expression was down-regulated when compared with the LIM group. From this study, we conclude that after injecting rhBMP2 into the vitreous cavity of experimental myopic guinea pigs, it can bind to BMP2-related receptors, activate smad signaling pathway, affect the expression of MMP2/TIMP2, promote the expression of Col1A1 gene, regulate scleral remodeling, promote collagen I synthesis, and delay the development of myopia.